2021
DOI: 10.1021/acsomega.1c00172
|View full text |Cite
|
Sign up to set email alerts
|

Design Principles for Manipulating Electrochemical Interfaces in Solid-State Supercapacitors for Wearable Applications

Abstract: Storage and delivery of electrical energy form the heart of the rapidly expanding domain of wearable electronics, with applications ranging from point-of-care medical diagnostics to Internet-of-Things (IoT). Solid-state, electrochemical, doublelayer-based supercapacitive energy storage devices, with high power density, ability to interface with intermittent energy harvesters, long lifetime, and cyclability, offer attractive possibilities for self-sustaining power sources in such portable applications. This min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…As promising candidates for supplying power, [ 175 ] SCs are supposed to possess high properties, as well as provide smart responsive functions, which can response to the variations from either the external circumstance or equipment themselves. [ 176 ] Intelligent functions, including self‐healing, [ 177 ] stretchability, [ 178 ] and shape memory [ 179 ] have been introduced into stimuli‐responsive equipment. [ 180 ]…”
Section: D Printed Supercapacitor For Various Applicationsmentioning
confidence: 99%
“…As promising candidates for supplying power, [ 175 ] SCs are supposed to possess high properties, as well as provide smart responsive functions, which can response to the variations from either the external circumstance or equipment themselves. [ 176 ] Intelligent functions, including self‐healing, [ 177 ] stretchability, [ 178 ] and shape memory [ 179 ] have been introduced into stimuli‐responsive equipment. [ 180 ]…”
Section: D Printed Supercapacitor For Various Applicationsmentioning
confidence: 99%
“…It is worth mentioning that the reported values in the literature are based on the active mass or the volume of electrodes instead of the total device mass or volume, as specified for commercial devices. Hence, SSCs are promising candidates for next-generation energy storage applications, particularly portable and wearable electronics, implementable medical devices, Internet of Things (IoT), 36 and smart textiles. 37,38 Several good reviews have been reported in the literature [37][38][39][40][41][42][43][44][45][46][47][48] ; however, these studies focus particularly on flexible SSCs, instead of giving the complete picture of the technology.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that the reported values in the literature are based on the active mass or the volume of electrodes instead of the total device mass or volume, as specified for commercial devices. Hence, SSCs are promising candidates for next‐generation energy storage applications, particularly portable and wearable electronics, implementable medical devices, Internet of Things (IoT), 36 and smart textiles 37,38 …”
Section: Introductionmentioning
confidence: 99%
“…[5,6] At a fundamental level, such stringent requirements translate to the holy grail of energy storage: high energy density and power density without compromising the lifetime. [7][8][9][10] Electrochemical double layer-based supercapacitors (EDLCs) operating on the basis of non-Faradic electrostatic charge build-up at the electrode-electrolyte interface and therefore exhibits high-rate capability, short relaxation time constant (τ), long lifetime, and high-power density compared to their Faradic counterparts. However, the low energy density and selfdischarge behavior of such systems severely restricts their usability in tandem with renewables.…”
mentioning
confidence: 99%